The unusual record of Nereites, wrinkle marks and undermat mining trace fossils from the late Silurian-earliest Devonian of central-western margin of Gondwana (Argentina) - Pazos, Pablo Jose (2015)
Silurian-Devonian deposits of central western Argentina contain one of the most diverse Palaeozoic records of Nereites in Gondwana. Nereites cf. cambrensis, Nereites irregularis?, Nereites jacksoni, Nereites macleayii, Nereites missouriensis and Nereites pugnus are documented in a turbidite-like succession of the San Rafael Block (Río Seco de los Castaños Formation). The succession, historically assumed as deep-sea deposits or interpreted as a deltaic system, also contains abundant microbially induced sedimentary structures (MISS) such as wrinkle marks. Glossy surfaces indicate abundant biofilms, where the fossil record comprises N. macleayii, N. missouriensis, scarce arthropod trackways (. Diplichnites?) and undermat-miner structures. Nereites, the pioneer colonizer, is in some cases cross-cut by Dictyodora, while undermat miners are the late bioturbators. The succession is dominated by gravity flow deposits, including storm related, turbidite-like deposits and abundant wrinkle marks. These suggest deposition on the shelf rather than the deep sea. This study shows that microbial mats were not restricted to marginal marine environments during the mid Palaeozoic, and documents one of the most diverse Palaeozoic records of Nereites in western Gondwana. It also contributes to the record of Nereites, Dictyodora, and Zoophycos found, for first time, in association with microbial mat structures in the late Silurian-earliest Devonian, the Nereites ichnofacies together with abundant wrinkle marks.